Engineering Education and Entrepreneurial Attitudes Among Students: Ascertaining the Efficacy of the Indian Educational System - Singh, Ajay; Singh, Shashi; Singh, Kiran (Prabandhan: Indian Journal of Management, 2015)
An attempt has been made with the help of this paper to recognize the entrepreneurial attitudes among students pursuing technical courses from institutes affiliated to Uttar Pradesh Technical University, Meerut, Uttar Pradesh. The present research paper aims to determine the roles of training at the secondary and graduation levels in familiarizing entrepreneurship as a career choice and boosting the interests among students to take up entrepreneurship as their preferred calling. In the present study, 206 scholars from different engineering courses were examined using the entrepreneurial attitude orientation scale. Outcomes indicate that a significant difference existed between the thinking of female and male students towards entrepreneurship. The respondents revealed that the approach of the education system does affect entrepreneurial orientation in an individual. Unfortunately, it was found that the Indian technical education system was not contributing significantly towards developing entrepreneurial orientation among students.